An Integrative Review of the Symptom Perception Process in Heart Failure. Issue 2 (March 2022) - Lee, Kyoung Suk; Oh, Seieun
Abstract : Background: Accurate symptom perception is a fundamentally essential component of self-care for patients with heart failure (HF) so they can make appropriate decisions about their symptoms. Objective: The purpose of this integrative review was to describe the pathways of the symptom perception process and its contributing factors in patients with HF. Methods: A comprehensive literature search was conducted using PubMed, EMBASE, and PsycINFO databases to identify studies describing the symptom perception process (symptom detection, comprehension, and response) in adult patients with HF. Results: Two pathways of the symptom perception process were identified from 42 articles: ideal and undesirable pathways. Patients in the ideal symptom perception pathway had a comprehensive understanding of HF and a firm belief in the importance of self-care, were vigilant, and possessed good decision-making skills. They also were able to successfully use their experiences for future care. However, patients in the undesirable symptom perception pathway had a limited understanding of HF with poor symptom monitoring skills and inaccurate judgments about symptoms. Diverse factors contributing to the symptom perception process were identified (eg, levels of understandings of HF and social support). Conclusion: Our review indicated that symptom perception was likely to diversify the pathway of HF management. A variety of contributing factors to the symptom perception process were found to be intertwined. The findings of our review can inform the development of best patient education practice, although further research needs to be conducted to understand why and how patients can follow the most appropriate path from their past experiences. Abstract : Supplemental digital content is available in the text.